Peranan Lagu Anak-Anak Sebagai Media Persuasif Untuk Mempengaruhi Perilaku Positif Anak Usia Dini Di Kota Surakarta - Dewi Agustini (Lisyabab : Jurnal Studi Islam dan Sosial, 2020)
Children's songs are usually cheerful and reflect noble ethics, poetry contains things that are usually done by children. Singing a child's song is a way that can be used as a medium for delivering messages or character education in the daily lives of young children (1-6 years). His intelligence is developing rapidly, which is usually called the "Golden Age". Can be used to stimulate aspects of development, especially their character and emotions. Can be used as a medium of education and delivery of messages. The most important thing can affect positive behavior if you often listen to it. So, children's songs are the right media to train and develop imagination and improve mood suddenly, will bring new worlds or new experiences, develop or sharpen their minds either cognitive or their emotions